Clinical dysphagia risk predictors after prolonged orotracheal intubation (Clinics, 2014)
OBJECTIVES: To elucidate independent risk factors for dysphagia after prolonged orotracheal intubation. METHODS: The participants were 148 consecutive patients who underwent clinical bedside swallowing assessments from September 2009 to September 2011. All patients had received prolonged orotracheal intubations and were admitted to one of several intensive care units of a large Brazilian school hospital. The correlations between the conducted water swallow test results and dysphagia risk levels were analyzed for statistical significance. RESULTS: Of the 148 patients included in the study, 91 were male and 57 were female (mean age, 53.64 years). The univariate analysis results indicated that specific variables, including extraoral loss, multiple swallows, cervical auscultation, vocal quality, cough, choking, and other signs, were possible significant high-risk indicators of dysphagia onset. The multivariate analysis results indicated that cervical auscultation and coughing were independent predictive variables for high dysphagia risk. CONCLUSIONS: Patients displaying extraoral loss, multiple swallows, cervical auscultation, vocal quality, cough, choking and other signs should benefit from early swallowing evaluations. Additionally, early post-extubation dysfunction recognition is paramount in reducing the morbidity rate in this high-risk population.